Evaluation of the scil vCell 5, a novel laser- and impedance-based point-of-care hematology analyzer, for use in dogs and cats - Zelmer, Kim-Lina Charlotte; Bauer, Natali; Moritz, Andreas; Justus Liebig University Giessen (My University, 2022)
A novel laser- and impedance-based point-of-care hematology analyzer (POCA), the vCell 5 (scil Animal Care), providing a complete blood count with 5-part leukocyte differential count has recently been introduced to veterinary laboratories. We evaluated the analyzer for use in dogs and cats including method comparison and assessment of linearity, carryover, and precision. Fresh blood samples from 192 healthy and diseased dogs and 159 cats were analyzed, and results were compared to reference methods (i.e., microhematocrit [PCV], Advia 2120 hematology analyzer). Total observed error (TEo) was calculated from CV, obtained at 3 concentrations, and bias%, and compared to total allowable error (TEa). For both species, excellent correlation (rs = 0.93–0.99) was seen between methods for WBC and RBC, hematocrit, hemoglobin, and platelet counts (PLT), except for feline PLT (rs = 0.79). Quality requirements (TEo < TEa) were fulfilled for WBC (TEo = 8.6–11.1%; TEa = 20%) and RBC (TEo = 3.5–7%; TEa = 10%), hematocrit (TEo = 5.7–9.4%; TEa = 10%), PCV (cat TEo = 7.8%; TEa = 10%), mean corpuscular volume (cat TEo = 5.1%; TEa = 7%), and PLT (TEo = 13.1–24.1%; TEa = 25%). Excellent linearity was demonstrated for WBC, RBC, and PLT, and hemoglobin. CVs of <2% for WBC, RBC, hematocrit, hemoglobin, and of <5% (dog) and 8% (cat) for PLT were demonstrated for values within the RI. Except for calculated variables and well-known species-specific deviations in feline PLT, scil POCA results were correlated favorably with reference method results and complied with quality requirements for cats and dogs.
Keywords: focused flow impedance; hematology; laser flow cytometry; linearity; method comparison; point-of-care analyzer; precision; total allowable error; ddc:630